Improving Mathematics Learning Outcomes Assisted by the Snakes and Ladders Game Media for Fifth Grade Elementary School - Stelawati, Yuyun; Iffatun, Khikma; Nur Azizah, Fiiki; Riswari, Lovika Ardana (Fakultas Tarbiyah dan Ilmu Keguruan, UIN Kiai Haji Achmad Siddiq Jember, 2023)
This research aims to improve and determine the feasibility of learning media for the mathematical snakes and ladders educational game tool by discussing the main volume of cubes and blocks. This research design uses the Classroom Action Research (PTK) model which uses 2 cycles in its implementation. The independent variable in this research is the learning media for the snakes and ladders game, with the dependent variable being the increase in student learning outcomes. The population in this study were students at SDN Jetak, with a research sample of 12 students. This research consists of 2 cycles, consisting of planning, implementation, monitoring and reflection. Learning is increased in cycle 2 if the indicators in cycle 1 have not achieved learning success. Data collection uses interview, observation and test techniques. Data analysis was carried out in three stages, data reduction, data presentation, and drawing conclusions. The results of the research show that the use of the snakes and ladders educational game learning media can improve learning outcomes and change attitudes towards the mathematics learning material volumes of shapes, cubes and blocks. The increase is shown by the average in cycle 1, namely 53.75 and increasing to 82.9 in cycle 2, which means an increase of 29.15 or the equivalent of 54.23%. Thus, it is concluded that the educational learning media game Snakes and Ladders can improve learning outcomes and change student achievement in learning. Learning using snakes and ladders media can make learning more active.